Biostatistics for the biological and health sciences - Triola, Marc M.; Triola, Mario F.; Roy, Jason (Jason Allen) (Hoboken, NJ : Pearson, 2024)
"Popular textbook that examines the relationship between statistics and our world through extensive use of a wide variety of real world applications that bring life to statistical theory and methods"--
Includes bibliographical references and index.
PHR
Karim International
Keywords: Biometry; Medical statistics; Pharmacy